DDRGK1-mediated ER-phagy attenuates acute kidney injury through ER-stress and apoptosis - Haijiao Jin; Yuanting Yang; Xuying Zhu; Yin Zhou; Yao Xu; Jialin Li; Chaojun Qi; Xinghua Shao; Jingkui Wu; Shan Wu; Hong Cai; Leyi Gu; et al. (Cell Death and Disease, 2024)
Abstract Acute kidney injury (AKI) constitutes a prevalent clinical syndrome characterized by elevated morbidity and mortality rates, emerging as a significant public health issue. This study investigates the interplay between endoplasmic reticulum (ER) stress, unfolded protein response (UPR), and ER-associated degradation (ER-phagy) in the pathogenesis of AKI. We employed four distinct murine models of AKI—induced by contrast media, ischemia–reperfusion injury, cisplatin, and folic acid—to elucidate the relationship between ER-phagy, ER stress, and apoptosis. Our findings reveal a marked decrease in ER-phagy coinciding with an accumulation of damaged ER, elevated ER stress, and increased apoptosis across all AKI models. Importantly, overexpression of DDRGK1 in HK-2 cells enhanced ER-phagy levels, ameliorating contrast-induced ER stress and apoptosis. These findings unveil a novel protective mechanism in AKI, wherein DDRGK1–UFL1-mediated ER-phagy mitigates ER stress and apoptosis in renal tubular epithelial cells. Our results thereby contribute to understanding the molecular underpinnings of AKI and offer potential therapeutic targets for its treatment.